How should chylothorax be managed?. Issue 6 (June 1987) - Puntis, J W; Roberts, K D; Handy, D
Abstract : The management and complications of chylothorax occurring beyond the neonatal period were reviewed retrospectively. Records from 15 patients treated between 1976 and 1986 were analysed; a combination of thoracocentesis, chest drain insertion, and dietary modification were successful in abolishing chyle leakage in 10 cases. One child died from complications of cardiac surgery rather than from the chylothorax, and surgical intervention was necessary in the remaining four patients and included pleurectomy in three and thoracic duct ligation in the fourth. Lymphopenia, hypoalbuminaemia, hyponatraemia, and weight loss were the most common complications of conservative management and tended to occur in those patients with the longest duration of drainage. Postoperative recovery after pleurectomy and thoracic duct ligation was uneventful. We conclude that conservative management of chylothorax will be successful in most cases. Complications of such a policy are fairly common but rarely serious.